Best Choice for Investment-Islamic Equity or Sukuk? - Akhmad Yusuf Khoiruddin (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2016)
Islamic capital market is an important part in the development of Islamic economics especially in providing a mobilization of fund to the efficient economic source and provides liquidity to the Islamic finance institution such as Islamic bank etc. There are two main instrumens in Islamic capital market namely Islamic equity and sukuk. In investmet point of view, the raise question is what is the best choises of investment between islamic equity and sukuk. The objective of this research to describe the return and the risk profile of Islamic equity and sukuk in the world. Second, this paper will conduct study about the chance to arrange Islamic portfolio investment consist of two securities namely, sukuk and Islamic equity. To analyze this, researchers will use some tools in capital market theories including portfolio theory, minimum variance portfolio, Sharpe, Jansen, Treynor and RAP model. Thirdly, this paper will test the different level of return between Islamic equity and sukuk. The main instrument is statistical analysis, and SPSS. This research found that based on quantitative analysis Sukuk provides a better return as well as lower risk. However, in the short term, islamic equity is often provide a higher return than sukuk. From the several measurement tools, this research also finds that sukuk has a better performance than islamic equity. In contrast, statistical testing shows that there are no significance differences return between Islamic equity and sukuk from 2005 till 2010. Therefore, this research suggest that investor/peple who want to increase their wealth and prefer to invest in islamic capital market, they should make a islamic portfolio include some securities component, sukuk, islamic equity, islamic unit trust, islamic etf, etc.